Incidencia de la aplicación de Open Office en el proceso de enseñanza aprendizaje en los estudiantes del centro educativo 1 de Noviembre de la ciudad de Pasaje Periodo Lectivo 2012-2013. - Morán Serrano, Mirian Yanine (2013)
This research aimed to determine the impact of the application of Open office in the teaching-learning process in students of the school on November 1, the Open Office package, which serve as study material to students inside and outside the classroom as well as supporting teachers teaching in the classroom, helping to improve the process of teaching and learning in this subject.